2018
DOI: 10.1021/acs.organomet.8b00440
|View full text |Cite
|
Sign up to set email alerts
|

Divergent Reactivity of CO2, CO, and Related Substrates at the Nickel Carbon Double Bond of (PCcarbeneP)Ni(II) Pincer Complexes

Abstract: The addition of carbon monoxide (CO), carbon dioxide (CO2) and isoelectronic isocyanide and isocyanates to the nickel carbene bond in PCcarbeneP pincer complexes is reported. For CO and CNR, irreversible group transfer reactions are observed, while for CO2, a reversible 2 + 2 addition to the carbene moiety occurs. The course of the CO and CO2 reactions are strongly affected by the nature of the PCcarbeneP pincer ligand framework, and a new more rigid ligand based on a 10,10-dimethyl-9,10-dihydroanthracene core… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 56 publications
1
20
0
Order By: Relevance
“…Although the mechanism for this bond cleavage was not investigated, this example is rather unremarkable, as rhodium complexes in the presence of PPh 3 have long been known to generate thiocarbonyls from CS 2 . In contrast to CS 2 , Piers has shown that CO 2 and tert ‐butyl isocyanate react with a nucleophilic nickel PC carbene P pincer complex to form metallabutylcycles, in which the C−O bond of CO 2 and the C−N bond of OCN t Bu are activated, but not completely cleaved …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the mechanism for this bond cleavage was not investigated, this example is rather unremarkable, as rhodium complexes in the presence of PPh 3 have long been known to generate thiocarbonyls from CS 2 . In contrast to CS 2 , Piers has shown that CO 2 and tert ‐butyl isocyanate react with a nucleophilic nickel PC carbene P pincer complex to form metallabutylcycles, in which the C−O bond of CO 2 and the C−N bond of OCN t Bu are activated, but not completely cleaved …”
Section: Methodsmentioning
confidence: 99%
“…31 P NMR analyses reveal that the half‐lives of these complexes to be a matter of hours at room temperature (t 1/2 2‐Int PPh3 <6 h, 2‐Int PPh2(C6F5) <1 h). These short half‐lives prevented structural characterization, however, PC carbene P pincer complexes have been shown to form adducts in a [2+2] fashion with isocyanates and carbon dioxide, and related sulfur tethered methandiide complexes reported by Gessner are known to also form [2+2] adducts with isocyanates and isothiocyanates . The identity of these short lived complexes prior to formation of 2‐L could presumably also be [2+2] ‘pre‐activation’ complexes.…”
Section: Methodsmentioning
confidence: 99%
“…Given that both Pt II and Pt IV salts and complexes are effective π‐acid catalysts, we sought to isolate well‐defined examples of cationic Pt II and Pt IV carbene complexes to probe the bonding in these important species. Hypothesizing that a strong ligand chelate may be able to support these species, we employed the rigid, 10,10‐dimethyl‐9,10‐dihydroanthracene‐derived PCP ligand framework L 1 , which is competent in the stabilization of analogous nickel(II) complexes . For comparison, an isostructural Pd II species was also prepared and it was shown that the Pt−C bonds are indeed more stable due to stronger π bonding, attributable to relativistic effects.…”
Section: Figurementioning
confidence: 99%
“…As both Pt(II) and Pt(IV) salts and complexes are effective π-acid catalysts, we sought to isolate well--defined examples of cationic Pt(II) and Pt(IV) carbene complexes to probe the bonding in these important species. Hypothesizing that a strong ligand chelate may be able to support these species, we employed the rigid, 10,10--dimethyl--9,10--dihydroanthracene-derived PCP ligand framework L 1 , 11 which is competent in the stabilisation of analogous nickel(II) complexes. 12 For comparison, an isostructural Pd(II) species was also prepared and it can be shown that the Pt--C bonds are indeed more stable due to stronger π bonding, attributable to relativistic effects.…”
Section: Chart 1 Known Platinum Alkylidenesmentioning
confidence: 99%